Comparative genome analysis across a kingdom of eukaryotic organisms: Specialization and diversification in the Fungi - Cornell, Michael J.; Alam, Intikhab; Soanes, Darren M.; Wong, Han Min; Hedeler, Cornelia; Paton, Norman W.; Rattray, Magnus; Hubbard, Simon J.; Talbot, Nicholas J.; Oliver, Stephen G. (Genome Research, 2007)
The recent proliferation of genome sequencing in diverse fungal species has provided the first opportunity for comparative genome analysis across a eukaryotic kingdom. Here, we report a comparative study of 34 complete fungal genome sequences, representing a broad diversity of Ascomycete, Basidiomycete, and Zygomycete species. We have clustered all predicted protein-encoding gene sequences from these species to provide a means of investigating gene innovations, gene family expansions, protein family diversification, and the conservation of essential gene functions—empirically determined in Saccharomyces cerevisiae—among the fungi. The results are presented with reference to a phylogeny of the 34 fungal species, based on 29 universally conserved protein-encoding gene sequences. We contrast this phylogeny with one based on gene presence and absence and show that, while the two phylogenies are largely in agreement, there are differences in the positioning of some species. We have investigated levels of gene duplication and demonstrate that this varies greatly between fungal species, although there are instances of coduplication in distantly related fungi. We have also investigated the extent of orthology for protein families and demonstrate unexpectedly high levels of diversity among genes involved in lipid metabolism. These analyses have been collated in the e-Fungi data warehouse, providing an online resource for comparative genomic analysis of the fungi.